2001
DOI: 10.2460/ajvr.2001.62.1008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enalaprilat on cardiorespiratory, hemodynamic, and hematologic variables in exercising horses

Abstract: Enalaprilat administration almost completely inhibited ACE activity in horses without changing the hemodynamic responses to intense exercise and is unlikely to be of value in preventing exercise-induced pulmonary hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Some studies have suggested that midazolam alone may increase animal agitation and aggressive behaviours in dogs (Clarke et al., 2014; Riviere and Papich, 2018). This stimulant effect is species‐dependent, so that in humans, pigs, cattle and goats, midazolam has sedative‐hypnotic effects (Mirakhur et al., 1984; Smith et al., 1991; Stegmann, 1998) but stimulant effects have been reported in dogs, cats and horses (Court & Creenblatt, 1992; Ilkiw et al., 1996; Muir et al., 1982; Siegenthaler et al., 2020). However, in the present study, midazolam did not cause any stimulating effect in any of the dogs, rather provided significant sedation, so that dogs could be easily manipulated and examined after injection.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that midazolam alone may increase animal agitation and aggressive behaviours in dogs (Clarke et al., 2014; Riviere and Papich, 2018). This stimulant effect is species‐dependent, so that in humans, pigs, cattle and goats, midazolam has sedative‐hypnotic effects (Mirakhur et al., 1984; Smith et al., 1991; Stegmann, 1998) but stimulant effects have been reported in dogs, cats and horses (Court & Creenblatt, 1992; Ilkiw et al., 1996; Muir et al., 1982; Siegenthaler et al., 2020). However, in the present study, midazolam did not cause any stimulating effect in any of the dogs, rather provided significant sedation, so that dogs could be easily manipulated and examined after injection.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of the prodrug enalaprilat is good and so is the bond to the ACE (Muir et al 2001, Gardner et al 2004. A possible cause of varying oral bioavailability of ACE inhibitors could depend on various transport mechanisms through the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, measurements obtained from different methods in horses were compared [9,20,29] with conclusions being drawn partially based on these results. Normality ranges obtained by one method [29] were assumed to be valid for other methods, and established as reference values.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods for measuring ACE in plasma and serum samples have been described for human beings. Some of these, which employ substrates such as hippuryl-histidyl-leucine (HHL) [14,20] and 3 H-hippuryl-glycyl-glycine [29] and use a change in ultraviolet absorbance to measure the kinetics [16], have previously been described for use in equine serum or plasma. Recently, Alves et al [1] validated the use of the fluorescence resonance energy transfer (FRET) substrate o -aminobenzoic acid-FRK(Dnp)P-OH (referred to as ABZ) [2] for assaying human ACE levels and established that there is a good correlation between a spectrophotometric method employing HHL as the substrate and the fluorimetric method using the ABZ substrate in humans [1,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation